Elementary Mathematics Teachers’ and Coordinators’ Perceptions about Teaching Problem Solving in North Lebanon Private Schools: an Exploratory Mixed Study - Amanatallah, Lina Ramez; Moukarzel, Dalal Michel (European Scientific Journal, ESJ, 2018)
The purpose of this mixed research study was to explore how teaching problem solving is taking place at the elementary level in north Lebanon private schools, and to understand the challenges students were facing from the teachers’ and coordinators’ perspective. Four instruments were used: An inventory sent to 273 private schools, a teacher’s questionnaire, a coordinator’s interview, and class observations. Findings revealed that out of 129 Mathematics teachers who responded to the inventory, 126 (97%) affirmed using active learning strategies (ALS). To examine how Mathematics teaching is taking place, five private English speaking schools were purposefully selected to participate in the study with five Mathematics coordinators and ten teachers. The results showed inconsistency between the inventory, coordinators’ interviews, teachers’ responses to the questionnaire, and class observations. While responses to the inventory and teachers ‘questionnaires showed that at least 60% of teachers use ALS, class observations revealed that teachers did not make use of strategies that engage students in learning or in monitoring their progress and understanding. Moreover, teachers’ and coordinators’ responses to some questions showed that students’ difficulties were due to two main reasons: language barrier and poor analytical skills. Recommendations for teachers’ training on specific active learning strategies and adequate English language usage to teach mathematics were suggested.